A construção da formação docente do campo e os desafios da inclusão do estudante surdo - NEVES, Miranilde Oliveira (Brazilian Journals Publicações de Periódicos, 2022)
Understanding the need for reflection and educational action based on the teachers training in the rural, with emphasis on the process of inclusion of deaf students, it’s one of the objectives of this article. The construction of teacher training of the rural has been a constant concern, due to the specificities that the rural presents and when we talk about inclusion and deafness, the problem is greater. This text, focused on the Public Policy Legislation for Rural Education, reflects the analysis of Skliar (2013), Caldart (2002, 2009), Quadros (2005, 2008), Molina (2017), Arroyo (2019), among other scholars and intends to contribute to the knowledge of the issue in focus. In the course of this investigation, it was inferred that the introduction of the Lawof Directives and Basis of National Education 9394/96 and the implementation of public policies such as PRONERA, the emergence of the National Institute for the Education of the Deaf, the establishment of Law 10.436, Decree 5,626/2005, Decree 7.352/2010 and the Brazilian Inclusion Law -Law 13.146 of 2015 were actions that favored more inclusive perspectives in the rural, but they contradict the withdrawal of social rights and the distructure of Rural schools.